Twin reversed arterial perfusion sequence: the heartless twin - Rao, Ashwin; Rao, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
To report a case of twin reversal arterial perfusion sequence and its management by means of laser coagulation of the vascular malformation in the placenta. Twin reversed arterial perfusion sequence is a rare form of twin to twin transfusion syndrome occurring primarily in Monochorionic monoamniotic twins. The prevalence is about 1 in 35,000 pregnancies. The significance of this condition is that there is a normal foetus and an acardiac foetus. The blood is shunted from the normal twin to the acardiac twin through vascular malformations in the placenta. The normal twin faces a high risk of both morbidity and mortality due to cardiac failure. A case of twin reversal arterial perfusion sequence diagnosed at 22 weeks following a target scan underwent laser photocoagulation and gave birth vaginally at 30 weeks without any complications. Early detection of this condition can lead to timely intervention and thereby improve the outcome. In Twin reversal arterial perfusion sequence, the normal or the pump twin has a high chance of mortality due to cardiac failure. As the size of the acardiac twin increases, there is a higher chance of mortality of the pump twin. There is a need for regular follow up with ultrasonography and foetal echocardiography along with early therapeutic interventions to ensure the survival of the normal twin. In our case, despite the large size of the acardiac twin, we had a successful pregnancy outcome for the normal twin due to timely intervention.